Chlamydia trachomatis infections and their impact in the adolescent population - Santalucía, Martín (2022)
Chlamydia trachomatis is an obligate intracellular organism and can only replicate inside eukaryotic host cells. It has a unique developmental cycle, with metabolically inert, spore‑like elementary bodies that infect host cells and develop into metabolically active, replicative or reticulate bodies (RBs) within a membrane‑bound inclusion. RBs are divided once more into elementary bodies 24 to 48 hours after infection and they are eventually released through lysis of the host cell. The chlamydial infection, like the gonococcal infection, is the possibility of severe sequelae in both the eye and the genital tract. Chlamydia trachomatis infects epithelial cells in the eye and genital tract. The early stage of infection can present with a mucopurulent discharge, but infections are often asymptomatic at this stage. In most infected women, the infection has a resolution, but in women with persistent or repeated infections, it can spread upwards from the endocervix to the fallopian tubes, leading to infertility or ectopic pregnancy because of tubal occlusion by scar tissue. It is a common etiologic agent in acute salpingitis, mainly in the adolescent’s population. With the exception of the lymphogranuloma venereum strains, which cause systemic illness and infect regional lymph nodes, Chlamydia trachomatis infection usually remains confined to mucosal surfaces, and it continues to produce enormous social and economic consequences despite advances in prevention, screening, and treatment.